STRUCTURE AND PERFORMANCE OF RICE SUPPLY CHAIN IN LUMAJANG REGENCY (Journal of Namibian Studies : History Politics Culture, 2023)
This study aims to identify the structure, pattern, flow, and performance of the rice supply chain. This research is descriptive and analytic research which was conducted purposively in Lumajang Regency. Sampling using the snowballing method, starting from grain farmers in Candipuro and Jatiroto districts. To understand the structure and flow of the rice supply chain using a “rich picture building”, to analyze the performance of the grain and rice supply chain, it is measured using the criteria of marketing margin and farmer’s share. The results showed that (1) the structure of the rice supply chain was farmers, grain traders, grain millers, rice traders, rice retailers, and rice consumers, (2) the rice supply chain patterns were five, namely (a) farmers – small grain weighers – grain milling – rice wholeselers – rice retailers – consumers, (b) farmers – small grain weighers – large grain weighers – grain milling – rice wholeselers – consumers, (c) farmers - large grain weighers - grain milling (outside Lumajang), (d) farmers (outside Lumajang) – large grain weighers - grain milling - rice retailers - consumers, (e) large grain weighers  (outside Lumajang) - grain milling - rice wholesalers – rice retailers – consumers, (3) there are three flow of rice supply chains, namely product flow that flows in one direction from grain farmers ending to rice consumers, financial flow flows in one direction from rice consumers ending to grain farmers and information flows in two directions. and (4) the performance of the grain and rice supply chain in all supply chain patterns is efficient. Short-supply chain pattern is more efficient.